Altering the environment to improve appointment system performance - CAYIRLI, Tugba (Institutional Knowledge at Singapore Management University, 2019)
Current research on clinicperformance is focused primarily on appointment scheduling rather than shapingthe clinical environments. The goal of this study is to investigate the impactof environmental factors on the total cost performance of a clinic, measured asa weighted sum of patients’ wait times and physician’s idle time and overtime.The environmental factors investigated include the variability of servicetimes, the probabilities of no-shows and walk-ins, the number of appointmentsper session and the cost ratio of physician’s time to patients’ time. The effectsof these factors are evaluated using a near-optimal rule that already adjuststhe patients’ appointment times to minimize the negative effects of thesefactors, so that their trueeffects on total cost performance can be isolated. As a result, this studyprovides useful insights tohealthcare practitioners in prioritizing their efforts in managing the different sources of variability to further improve the clinic performancebeyond the use of an optimal or near-optimal appointment rule. Additionalexperiments are conducted on the effects of patient and physicianunpunctuality, which have been studied to a lesser extent in priorliterature.